2023
DOI: 10.3390/ani13061095
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Stress Caused by Environmental Changes for Improving the Welfare of Laboratory Beagle Dogs

Abstract: Animal stress is influenced by environmental factors, yet only a few studies have evaluated the effects of environmental stress on captive dogs. This study aimed to evaluate the effects of environmental and social enrichment on the stress levels of captive dogs housed in a lab. We assessed stress levels in eight Beagle dogs by measuring their body weight, cortisol levels, a stress hormone, the alkaline phosphatase activity in serum, the number of steps per hour, as well as clinical sign observations in a chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…While most of the living conditions for Korean MWDs are spacious, comfortable, and well-managed, this may not be the case for all units. Previous studies have shown that human interaction and environmental enrichment can reduce stress in dogs living in kennels, such as laboratory dogs, shelter dogs, and working dogs [ 43 , 46 , 47 ]. Maintaining a positive relationship with handlers and improving the kennel environment may help prevent eating behavioral disorders.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the living conditions for Korean MWDs are spacious, comfortable, and well-managed, this may not be the case for all units. Previous studies have shown that human interaction and environmental enrichment can reduce stress in dogs living in kennels, such as laboratory dogs, shelter dogs, and working dogs [ 43 , 46 , 47 ]. Maintaining a positive relationship with handlers and improving the kennel environment may help prevent eating behavioral disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Five individual questions in the C-BARQ (S) were generated by combining two separate questions in the long questionnaire into a single question. Examples that follow are five individual questions in the C-BARQ (S) with modified words in italics and original words in italics and parentheses: [ 1 ] “Aggressive when approached directly by an unfamiliar person while being walked/exercised on a leash” (one question for adult and one for child in the C-BARQ); [ 2 ] “Aggressive when approached directly by an unfamiliar dog while being walked/exercised on a leash” (one question for male and one for female identifiers placed before “dog” in the C-BARQ); [ 3 ] “Afraid or anxious when approached directly by an unfamiliar person while away from your home” (one question for adult and one for child in the C-BARQ); [ 4 ] “Afraid or anxious when approached directly by an unfamiliar dog” (one question for same or larger size and one for smaller size identifiers placed before “dog” in the C-BARQ); and [ 5 ] “ Barking/whining when left alone for any period of time” (one question for barking and one for whining in the C-BARQ).…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral profiles of companion animals are often determined via direct observation by researchers, trainers, veterinarians and pet owners [ 1 , 2 ]. However, direct observation of animals like dogs can be complicated by various factors including the presence of a human observer [ 3 ] or restricted environments such as a veterinary setting [ 4 ] or laboratory kennels [ 5 ], which can elicit unintended responses from animals under observation [ 6 ]. Because of these factors, questionnaires, such as the frequently used Canine Behavioral Assessment and Research Questionnaire (C-BARQ), that ask dog owners about their dog’s responses to everyday stimuli or situations are increasingly used to obtain information about the behavior and temperament of pet dogs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Otro aspecto relevante es la reducción del estrés oxidativo, la cirugía y el estrés asociado pueden incrementarlo de forma significativa en el organismo del perro, caracterizado por una producción excesiva de radicales libres que pueden causar daño celular (Fan et al, 2023). Al mantener una adecuada oxigenación, se contribuye a reducirlo promoviendo un equilibrio redox saludable, lo que favorece la recuperación y disminuye el riesgo de complicaciones postoperatorias (Lee et al, 2023).…”
Section: Importancia De La Oxigenación Postquirúrgicaunclassified